OPTIMALISASI SISTEM PEMELIHARAAN PADA GEDUNG SEKOLAH BERBASIS PENGGUNA GEDUNG (Studi Kasus SMA Negeri 2 Meulaboh) - Rita Fazlina; Rinaldy; Setiawan, David; Veranita; Amir, Astiah; Dinda, Raina Parmitalia; Zulyaden (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
In an effort to maintain the condition of the school building in order to remain in good condition, it is necessary to carry out routine maintenance. The purpose of this study was to determine the level of participation of users of the SMAN 2 Meulaboh building on routine maintenance. This research uses descriptive qualitative research. Primary data collection is obtained by observation, interviews, documentation, and distributing questionnaires, while secondary data is obtained from related institutions or institutions. Data analysis was processed using the Likert Scale method. The sampling technique used is proportionate stratified random sampling. The results of the analysis obtained are 81 students (95.294%) are in the medium participation category, 4 students (4.706%) are in the high participation category, 21 teachers (70%) are in the moderate participation category, 9 teachers (30%) is in the high participation category, for 9 school staff and 1 school custodian, the results obtained are 6 respondents (60%) are in the medium participation category, 4 respondents (40%) are in the high participation category, and none of the respondents are in the low participation category.